983. Outcomes of Candida Bone and Joint Infections in Eight Patients from a Phase 3 Open-label Study (FURI). (4th December 2021) - Sanders, John W; Morse, Caryn; Cornely, Oliver; Koehler, Philipp; Krause, Robert; Prattes, Jürgen; Weiss, Guenter; Azie, Nkechi; Angulo, David A
Abstract: Background: Candida osteoarticular infections are often preceded by candidemia with the intervertebral discs and knee joints the most common area for candidemic seeding. Candida osteomyelitis has significant morbidity and diagnosis is often delayed difficult to treat. Treatment courses are usually long and there are limited oral options available for patients who have an azole-resistant infection. Oral ibrexafungerp is an investigational broad-spectrum glucan synthase inhibitor antifungal with activity against Candida and Aspergillus species, including azole- and echinocandin-resistant strains. A Phase 3 open-label, single-arm study of ibrexafungerp (FURI; NCT03059992) is ongoing for the treatment of patients with fungal disease refractory or who intolerant of to standard of care antifungal therapy. Table 1. FURI Bone and Joint Infection Outcomes Methods: FURI subjects were eligible for enrollment if they have proven or probable, severe mucocutaneous candidiasis, invasive candidiasis or invasive aspergillosis and documented evidence of failure to, intolerance to, or toxicity related to a currently approved standard-of-care antifungal treatment or can not receive approved oral antifungal options (e.g., susceptibility of the organism) or a continued IV antifungal therapy is clinically undesirable or unfeasible. Results: An independent Data Review Committee (DRC) provided an assessment of treatment response for a total 74 subjects enrolled in the FURI study from 22 centers in US, UK and EU treated with ibrexafungerp for mucocutaneous or invasive fungal infections from 2016- 2020. There were 8 subjects out of the 74 subjects who were diagnosed with various bone and joint infections, 5 subjects with spondylodiscitis, 1 subject with a knee/prosthetic joint infection and 2 subjects with bone infections, one of the tibia and one of the zygomatic arch. Table 1 shows outcomes for this patient group, five (75%) patients had a clinical benefit (complete or partial response and stable response), one (12.5%) had progression of disease and one patient was indeterminate. The median days of therapy for this group was 210.5 days. Conclusion: Analysis of 8 subjects from the FURI study indicates that oral ibrexafungerp provides a promising therapeutic response in option for patients with bone and/or joint infections. Disclosures: Caryn Morse, MD, Chimerix (Scientific Research Study Investigator)Covis Pharma (Scientific Research Study Investigator)Gilead Sciences Inc. (Scientific Research Study Investigator)Ridgeback Biotherapeutics (Scientific Research Study Investigator)Roche (Scientific Research Study Investigator)SCYNEXIS, Inc. (Scientific Research Study Investigator)Theratechnologies (Advisor or Review Panel member)Viiv (Advisor or Review Panel member) Oliver Cornely, Prof., Actelion (Consultant, Grant/Research Support)Al-Jazeera Pharmaceuticals (Consultant)Allecra Therapeutics (Consultant)Amplyx (Consultant, Grant/Research Support)Astellas (Consultant, Grant/Research Support)Basilea (Consultant, Grant/Research Support)Biocon (Consultant)Biosys (Consultant)Cidara (Consultant, Grant/Research Support)CoRe Consulting (Consultant)Da Volterra (Consultant, Grant/Research Support)DFG (German Research Foundation ) (Grant/Research Support)Entasis (Consultant)F2G (Consultant, Grant/Research Support)German Federal Ministry of Research and Education (Grant/Research Support)Gilead (Consultant, Grant/Research Support)Grupo Biotoscana (Consultant)Immunic (Grant/Research Support)IQVIA (Consultant)Janssen (Grant/Research Support)Matinas (Consultant)Medicines Company (Grant/Research Support)MedPace (Consultant, Grant/Research Support)Melinta Therapeutics (Grant/Research Support)Menarini (Consultant)Merck/MSD (Consultant, Grant/Research Support)Molecular Partners (Consultant)MSG-ERC (Consultant)Mylan (Consultant)Nabriva (Consultant)Noxxon (Consultant)Octapharma (Consultant)Paratek (Consultant)Pfizer (Consultant, Grant/Research Support)PSI (Consultant)Roche Diagnostics (Consultant)Scynexis (Consultant, Grant/Research Support)Seres (Consultant)Shionogi (Consultant)Wiley (Blackwell ) (Other Financial or Material Support) Philipp Koehler, MD, Ambu GmbH (Consultant, Speaker's Bureau)Astellas Pharma (Speaker's Bureau)Euopean Confederation of Medical Mycology (Speaker's Bureau)German Federal Ministry of Research and Education (Grant/Research Support)Gilead (Consultant, Speaker's Bureau)MSD (Speaker's Bureau)Noxxon N.V. (Consultant)Pfizer (Speaker's Bureau)State of North Rhine-Westphalia, Germany (Grant/Research Support) Jürgen Prattes, Dr, AbbVie Inc. (Shareholder)Gilead (Speaker's Bureau)MSD (Grant/Research Support)Novo Nordisk (Shareholder)Pfizer (Advisor or Review Panel member)Stryker (Shareholder) Guenter Weiss, MD, MSD (Speaker's Bureau)Novartis (Speaker's Bureau)Pfizer (Speaker's Bureau)Pharmacosmos (Speaker's Bureau)Scynexis (Scientific Research Study Investigator)Vifor (Speaker's Bureau) Nkechi Azie, MD, SCYNEXIS, Inc. (Employee, Shareholder) David A. Angulo, MD, SCYNEXIS, Inc. (Employee, Shareholder)